2020
DOI: 10.1007/s11136-020-02480-y
|View full text |Cite
|
Sign up to set email alerts
|

The association between physical activity, sleep, and quality of life in patients in bio-chemical remission from Cushing’s syndrome

Abstract: Purpose Cushing's syndrome can negatively affect patient's quality of life (QoL) after treatment and remission. Exposure to increased cortisol over time can result in visceral obesity, which makes this population vulnerable to cardiovascular risk factors associated with visceral obesity. Sleep disturbances are present in patients in remission from Cushing's syndrome, impacting QoL. Moderate intensity physical activity performed 3 times a week decreases visceral obesity and improves sleep quality, therefore, en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Eight (22%) studies reported pre−/post‐surgery outcomes 18,19,37,38,42,43,47,48 . Thirty‐one (84%) studies reported HRQoL using validated patient reported outcome (PRO) measures 15,16,19,21,23–45,55–57 . A comprehensive list of the PRO measures used to measure the outcomes was recorded (Table A4).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Eight (22%) studies reported pre−/post‐surgery outcomes 18,19,37,38,42,43,47,48 . Thirty‐one (84%) studies reported HRQoL using validated patient reported outcome (PRO) measures 15,16,19,21,23–45,55–57 . A comprehensive list of the PRO measures used to measure the outcomes was recorded (Table A4).…”
Section: Resultsmentioning
confidence: 99%
“…CS specific HRQoL was evaluated in 18 (49%) studies using three different PRO measures—CushingQoL questionnaire, Tuebingen Cushing's Disease Quality of Life Inventory (Tuebingen CD‐25) and QoL‐Cushing's disease (QoL‐CD) 19,22–24,26,29–31,33–40,42,43,46 . CushingQoL is a 12‐item, CS‐specific HRQoL PRO that examines patients' HRQoL over the past 4 weeks 8 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the last decades these most distressing neurocognitive complaints have been increasingly described, like loss of memory, difficulties in concentration, coping with emotions and with executive functions, intolerance to stress, emotional incontinence, irritability, anxiety and depression, that negatively impact on health-related quality of life (QoL), which despite improving after adequate therapy to control hypercortisolism, may not normalize [ 1 6 ]. Furthermore, other persisting problems like sleep disturbances, fatigue, muscle weakness and permanent weight gain contribute to explain why patients with “cured” Cushing disease (CD) or any kind of endogenous Cushing syndrome (CS) still do not feel well [ 2 7 ].…”
Section: Introductionmentioning
confidence: 99%